ANALISIS ASPEK KEUANGAN DAN ASPEK PEMASARAN UNTUK MENILAI KELAYAKAN USAHA PADA UMKM BURGERAK DI KOTA AMBON - Windy; Sitra Yani Belasa; Christina Sososutiksno; Pranatalindo Simanjuntak; Muza Syahraini Prabowo; Nurlina Belasa; Afni Rahman (Jurnal Multidisipliner Kapalamada, 2025)
This study is motivated by the increasing competition of fast food MSMEs in Ambon City, so it is necessary to identify and evaluate the financial conditions and marketing strategies to ensure business sustainability. This study aims to identify and analyze the financial and marketing aspects in determining the feasibility of a business or business in the "Burgerak" MSME in the culinary field. The establishment of this business is an innovation from the business owner who sees the large business opportunities due to the lack of food trends in Ambon City. The method used in this study is a quantitative descriptive approach by obtaining data from interviews, observations, documentation, and simple financial reports. Business feasibility analysis is carried out using net profit indicators, payback period (PP), Net Present Value (NPV), and Profitability Index (PI). The results of the study show that Burgerak MSMEs are financially viable with stable profits, and have a fairly effective marketing strategy in reaching local consumers. However, increasing product innovation and expanding promotional reach are still needed to strengthen the business position in the Ambon culinary market.